Optimization of processing parameters of red gypsum-based brick manufacturing using response surface methodology - Mohd Amirul Hakim, Sidek; R. M., Yunus; Ahmad Khan, Mohamad Al-Nizar Khan; Islam, Muhammad Remanul (Asian Online Journals, 2019)
The red gypsum (RG) is a waste, industrial by product, can be potentially used for brick manufacturing. In the current study, the manufacturing of bricks using RG, sand and cement was optimized using response surface methodology (RSM). The water/cement (w/c) ratio and sand replacement were varied for an optimum compressive strength and water absorption properties of the cement. From the analysis, the average compressive strength of conventional cement brick (CCB) tested was 10.9 MPa. Based on the optimum solution from the RSM,analysis, possible cost prediction was estimated which can provide some valuable information to the manufacturer.